STRATEGI DAKWAH WAHDAH ISLAMIYAH DALAM MENGURANGI BUTA AKSARA AL-QUR’AN PADA KELOMPOK PENGAJIAN HAYAT KAMAL KECAMATAN SOMBA OPU KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This study aims to determine Wahdah Islamiyah's da'wah strategy in reducing al-Qur'an illiteracy in the Hayat Kamal study group, Somba Opu District, Gowa Regency, with sub-problems obtained as follows: 1) what are Wahdah Islamiyah's strategic steps in gathering participants for the Hayat Kamal study in Somba District, Gowa Regency? 2) How is Wahdah Islamiyah's da'wah method in teaching the Qur'an to Hayat Kamal recitation participants in Somba Opu District, Gowa Regency? 3) what are the obstacles faced in the process of learning the Qur'an? The type of research used is descriptive qualitative research. The approach used is the da'wah management approach and the sociological approach with data collection methods through observation, in-depth interviews, and documentation. Data processing and analysis techniques were carried out through several stages, namely: data condensation, data presentation, verification, and drawing conclusions. The results showed that Wahdah Islamiyah's da'wah strategy in gathering Hayat Kamal recitation participants went through several stages, namely: making a personal approach to the community, approaching the board and members of the taklim assembly, listing participants who wanted to join the recitation group, then determining the schedule for the initial meeting. . The da'wah methods used in the implementation of learning are: 1) Dirosa, 2) Tarbiyah, 3) Rihlah, namely natural tadabbur activities and 4) Joint Day.